International trade and plastic waste in oceans: legal and policy challenges - Hui, Zhang; Haider, Aftab; Khan, Asif (Frontiers in Marine Science, 2025)
Plastic waste pollution in oceans has emerged as a severe global crisis, exacerbated by international trade. The increased movement of goods, particularly plastic-based products, contributes significantly to marine plastic pollution. This study explores the intersection of international trade and plastic waste, focusing on legal and policy challenges. Using a qualitative research design, this paper reviews international legal frameworks such as the Basel Convention, the United Nations Convention on the Law of the Sea (UNCLOS), and regional trade agreements to assess their effectiveness in addressing plastic waste issues. The research highlights critical enforcement gaps, lack of standardized regulations, and insufficient international cooperation as major obstacles to effective plastic waste management. Key findings suggest strengthening international legal frameworks, enhancing monitoring and compliance mechanisms, and promoting sustainable trade practices are crucial for mitigating plastic pollution in oceans. The study underscores the necessity for binding agreements within trade policies to ensure a sustainable balance between economic growth and marine ecosystem preservation.